Pro Web Gadgets Across iPhone, Android, Windows, Mac, iGoogle and More - Udell, Sterling. (Apress, 2009)
The miniature web applications known as gadgets (or widgets) are a key component of the distributed web and an ideal way to publish your content far beyond the reach of your own web site. Packaging web content and functionality into a gadget enables it to be seen anywhere from iGoogle to the iPhonewherever the user may be, on or off the traditional web. Everyone can access your content without having to visit your web site. This book is a practical guide to building gadgets that will work everywhere, from handheld devices to any site on the web. The core methodology is to develop a single code base that will run on all platforms, multiplying the syndication opportunities for maximum return on your development investment. Extending this approach is a technique of abstracting key API calls from the various gadget platforms into a single interface layer, implemented in the book as a compact JavaScript class, allowing your gadgets full access to every platform's power without your having to rewrite your code for each. Learn the key concepts for successfully syndicating web content via gadgets. Build platform-agnostic gadgets that run on all the major web portals. Deploy your gadgets to web-enabled handheld devices.